Principles for choosing bariatric interventions (review of literature) - S. G. Balandov; D. I. Vasilevsky; K. A. Anisimova; Z. M. Khamid; D. V. Shkredov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
Currently, bariatric (metabolic) surgery is the main effective treatment of obesity and associated pathological conditions. The features of the course of obesity as a chronic progressive disease, heterogeneous etiology, clinical manifestations and a steady increase in number of patients worldwide make the problem of bariatric interventions extremely urgent. The article presents the analysis of modern data concerning the choice of the method of surgical benefits in patients with obesity and their own clinical experience.